Separate evaluation of the ipsilateral and contralateral MR fetal lung volume in patients with congenital diaphragmatic hernia - Henzler, Claudia; Burger-Scheidlin, Stefan; Weis, Meike; Weiß, Christel; Schönberg, Stefan; Schaible, Thomas; Neff, Wolfgang (American journal of roentgenology, 2016)
Objective. Our study had two objectives. First, we separately evaluated observed-to-expected MR fetal lung volume (FLV) of lungs ipsilateral and contralateral to a congenital diaphragmatic hernia (CDH). Second, we compared the prognostic value of observed-to-expected MR FLV of the ipsilateral and contralateral lungs with that of observed-to-expected MR FLV of both lungs with respect to survival, need for extracorporeal membrane oxygenation (ECMO), and development of chronic lung disease (CLD). Materials and methods. We evaluated observed-to-expected MR FLV of the lung ipsilateral to the diaphragmatic defect as well as in the contralateral lung in 107 fetuses with isolated CDH. ROC analysis and logistic regression analysis were performed to assess the prognostic value of the observed-to-expected MR FLV for association with outcome. Results. In all fetuses with CDH, values in the ipsilateral (mean observed-to-expected MR FLV ± SD, 9.4% ± 9.6%) and the contralateral lung (mean observed-to-expected MR FLV, 48.9% ± 18.5%; p < 0.0001) were significantly lower than values measured in healthy fetuses. Observed-to-expected MR FLV of both lungs and of the contralateral and ipsilateral lung revealed significant differences regarding survival (p < 0.0001, p < 0.0001, and p = 0.0170, respectively), need for ECMO (p < 0.0001, p < 0.0001, and p = 0.0051, respectively), and development of CLD (p = 0.0004, p = 0.0002, and p = 0.0460, respectively). Compared with the observed-to-expected MR FLV of both lungs, the observed-to-expected MR FLV of the contralateral lung showed a slightly higher prognostic accuracy regarding survival (AUC = 0.859 vs 0.825) and development of CLD (AUC = 0.734 vs 0.732) and a similar prognostic accuracy regarding need for ECMO (AUC = 0.805 vs 0.826). Observed-to-expected MR FLV of the ipsilateral lung did not show good prognostic value regarding survival (AUC = 0.617), need for ECMO (AUC = 0.673), and development of CLD (AUC = 0.636). These AUCs were significantly smaller than the AUCs resulting from the observed-to-expected MR FLV of both lungs (each p < 0.05) and considerably smaller than the AUCs of the observed-to-expected MR FLV of the contralateral lung (each p < 0.10). Conclusion. Patients with CDH showed a substantially lower observed-to-expected MR FLV of both lungs compared with healthy fetuses. The observed-to-expected MR FLV of both lungs as well as of the lung contralateral to the CDH were reliable prenatal predictors of survival, need for ECMO, and development of CLD.
Gesehen am 18.07.2019